Guest benefits of hedonic value and perceived community value drive hotel CSR participation. Issue 6 (3rd June 2022) - Butcher, Ken; Chomvilailuk, Rojanasak
Abstract: Successful promotion of guest participation in Corporate Social Responsibility (CSR) activities for the hedonic context of a hotel stay is challenging, especially where the CSR activity requires substantial guest involvement. Moreover, understanding of this issue becomes increasingly important as investment by hotels on CSR engagement strategies that include guests directly participating in such activities grows. While perceived benefits of guest participation are critical to optimizing CSR participation strategies, studies explicitly investigating guests' evaluation of costs versus benefits are lacking. Using an experimental scenario based on a guest's return to a hotel recently visited, a self-oriented hedonic benefit, a other-oriented benefit of perceived community value, and perceived time constraint were tested for their effects on guest CSR participation. Data was obtained from respondents in the US and Thailand. Analysis using structural equation modeling (SEM-PLS) demonstrated that a hedonic value benefit had a substantial direct effect on guest CSR participation while the effect from perceived community value was fully mediated by CSR reputation. The effect of perceived constraints on CSR participation was significantly stronger for US respondents. Findings present insights for hotel managers, policy makers, non-government agencies with a mission to promote CSR practices and researchers.